Pelaksanaan Community Based Corrections: Studi Kasus Di Lembaga Pemasyarakatan Terbuka Kelas IIB Nusakambangan - Hendro Setiyono, Ana Melia; Irvan Sebastian Iskandar (Esensi Hukum, 2025)
Overcrowding that occurs in correctional institutions encourages the need for alternatives to punishment that are more effective and oriented towards social reintegration. Community Based Corrections (CBC) is a new approach in the correctional system that is relevant to be implemented in the Nusakambangan Class IIB Open Prison. This study aims to analyze the implementation of Community Based Corrections in the Class IIB Nusakambangan Open Prison as a form of coaching that emphasizes the reintegration and rehabilitation of prisoners. The method used is a juridical-sociological approach with qualitative descriptive techniques, through document studies, interviews, and observations of the implementation of the CBC program. The results show that the implementation of CBC in Nusakambangan Open Prison has fulfilled basic principles such as community protection, proportionality, cost effectiveness, and restoration, although it still faces challenges in supervision and community participation. This research shows that CBC has the potential to become a future punishment policy that is more humane and efficient, and supports a correctional system that is oriented towards recovery and social integration.